2006
DOI: 10.1017/s1355617706060450
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating a theory of stress and adjustment when predicting long-term psychosocial outcome after brain injury

Abstract: Kendall and Terry (1996) include many psychosocial predictors in their theoretical model that explains individual differences in psychosocial adjustment (Lazarus & Folkman, 1984). The model depicts appraisal and coping variables as mediating relationships between situation factors, environmental and personal resources, and multidimensional outcome. The aim of this study was to explore these theoretical relationships at very late stages of recovery from traumatic brain injury. A total of 131 participants who we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
23
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(24 citation statements)
references
References 37 publications
1
23
0
Order By: Relevance
“…It should be emphasized that future research is needed to further investigate the relation between rehabilitation and these variables [42]. It is therefore necessary to take these variables into account if we are to improve the rehabilitation of TBI patients.…”
Section: Resultsmentioning
confidence: 99%
“…It should be emphasized that future research is needed to further investigate the relation between rehabilitation and these variables [42]. It is therefore necessary to take these variables into account if we are to improve the rehabilitation of TBI patients.…”
Section: Resultsmentioning
confidence: 99%
“…In the chronic stage after brain injury, this positive association was already known. 6,7,9 Furthermore, increasing self-efficacy seemed to mitigate the negative influence of emotion-oriented coping on health-related QOL, suggesting that high self-efficacy has a protective effect. This stress-buffering effect of high self-efficacy is well documented in healthy people 33 and patients with cancer.…”
Section: Discussionmentioning
confidence: 97%
“…6 As a general concept, higher general self-efficacy has been related to better QOL and social participation in TBI. [7][8][9] However, because all studies were conducted cross-sectionally in the chronic stage after TBI, one cannot determine whether self-efficacy in the early stage after brain injury is predictive for better long-term QOL and social participation.…”
mentioning
confidence: 99%
“…Lifestyle stressors have been found to influence emotional adjustment in long-term TBI (Rutterford & Wood, 2006); however, the emotional impact of early transition events after TBI has been largely overlooked. Research by Turner et al (2009) identified that individuals with brain injury viewed the hospital-to-home transition more favorably when greater progress was made in resuming their preinjury lifestyle.…”
Section: Introductionmentioning
confidence: 99%